Realising women's empowerment in patriarchal Haryana - through the lens of state initiated scheme. (2017) - Mathur, Deepali; Popli, Ushvinder Kaur
The present paper is a study on State initiated women's empowerment scheme named Sakshar Mahila Samooh (SMS). It is a group of rural literate women in each village as resource pool for the development of village community. One SMS was selected using purposive sampling to understand the scheme and to study the process of empowerment through qualitative approach. In-depth interviews of 25 members of SMS were taken and analysed manually to draw the factors responsible in the process of empowerment. The study found that the approach of SMS is more integrated since it has psychosocial empowerment as the base and economic empowerment as the outcome. Increased participation is leading to social action in the form of demonstrations and formation of sustained economic self help groups. The study shows that critical consciousness through support groups and psychosocial, health and legal awareness may ignite the realisation of oppression and develop alternative action.